ANALISIS PENGARUH CITRA MEREK, PERSEPSI KUALITAS, DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN MELALUI PERSEPSI NILAI SEBAGAI INTERVENING - Agvi Ramadhan Kurniawan (Faculty of Economics and Business Diponegoro University, 2015)
High population growth and the high mobility of the people and coupled with high carownership aspirations cause increased competition in the automotive industry.Automotive industry competition increased, causing the Honda Freed products lesscompetitive with other products in the class MPV cars. This study aimed to examine theeffect of brand image variables, perceived quality, and perceived risk on purchasingdecisions Honda Freed in Semarang through the perception of value as intervening.The total sample of 100 respondent owners and users of the Honda Freed is taken with aconvenience / accidental sampling technique. Method of data analysts using path analysismethod, the analysis includes: validity, reliability, classic assumption test, linearregression test, t test, F test, and Sobel test coefficient of determination.The results of path analysis showed that the two independent variables, namely the brandimage (0,382) and perceived quality (0,267) had a positive and significant relationship tothe intervening variable that is the perception of value. There is one independent variablethat has a negative relationship to the intervening variable is the perception of risk (-0,352). Intervening variables such as perceived value has a positive correlation (0,475)and parallel to the dependent variable.Keywords: perception of risk, brand image, perceived value, and purchase decision